AN ANALYSIS OF STUDENTS’ DIFFICULTIES IN UNDERSTANDING DESCRIPTIVE TEXTS AT THE SECOND YEAR OF SMAN 3 LANGGAM - Selvia Mardiani; Jismulatif Jismulatif; Erni Erni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research was aimed to find out students’ difficulties in understanding descriptive texts at the second year of SMAN 3 Langgam. This is descriptive quantitative research. The population of this research was the whole students of the second year of SMAN 3 Langgam. The sample of this research was 34 students of XI IIS 1 class who have been selected by using the cluster-random-sampling technique. The data were collected by using tests and questionnaires. The test consisted of 40 questions and the questionnaire consisted of 25 questions. The findings of this study based on the percentage of incorrect answers of reading test showed that there are eight components of reading comprehension. Six of them were categorized high level as difficult question aspects for the students. There were difficulties in identifying vocabulary, generic structure, factual information, reference, language features, and social function. Two of them were categorized medium level as a not difficult question. There was difficulty in identifying the main idea and inference. Based on the result of the questionnaire, the students felt difficulties in understanding descriptive texts because of internal and external factors. There was limited vocabulary knowledge, weak verbal reasoning, problems with recalling information, difficulty understand the text because of the level of the text, lack of familiarity with the subject matter, lack of fluency in reading, problems with processing information after reading, and inadequate use of reading strategies in the teaching and learning process.Key Words: Analysis, Students’ Difficulties, Reading, Descriptive Text.